GOOD SELF INTEREST DAN RISIKO TINDAKAN FRAUD: KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI - Novira Sartika; Sri Rahayuni (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2022)
This study aims to determine the effect of good self-interest on the risk of fraud with organizational commitment as a mediating variable at the Regional Apparatus Organization (OPD) in Bengkalis City. This study uses a quantitative approach and primary data. The population in this study were employees at OPD in Bengkalis City with the total sample are 78 respondents using purposive sampling technique with the criteria of employees with functional tenure more than 2 years. The data were analyzed using path analysis with the help of SPSS Version 25. The results showed that good self-interest has a significant effect on the risk of fraud with organizational commitment as a mediating variable. So, the higher good self-interest and added the organizational commitment of an employee, can decrease the risk of fraud because the employee will do the best for the organization.